Efficacy of TheraCal LC and Biodentine as Direct Pulp Capping Agents - An Clinico-Histological Study - Joshi Poonam; Rajasekhar Reshma; Saoji Sumant V; Richhawal Anil; Punia Jasleen K (Wolters Kluwer Medknow Publications, 2024)
AimTo assess clinically and histologically the efficacy of TheraCal LC and Biodentine as Direct Pulp Capping agents. Materials and MethodSixty caries-free maxillary first premolar teeth which were scheduled for orthodontic extraction were selected for the study and were divided equally into Group 1 (Theracal LC) and Group 2 (Biodentine). Thermal and electric pulp testing was performed on the teeth to assess pulp vitality followed by tooth preparation to expose pulp horns under local anesthesia. After achieving hemostasis, the direct pulp capping agent was placed and composite restoration was done. All the teeth were evaluated and compared in terms of clinical and histological findings after 6 weeks. The statistical analysis used was the Kruskal-Wallis test. ResultsTeeth with Theracal LC showed no sensitivity to heat, cold, or percussion, whereas sensitivity to heat, cold, or percussion was noted with Biodentine. Histological evaluation revealed that TheraCal LC has higher efficiency in complete dentin bridge formation, had maximum dentin thickness, and showed minimal or no pulpal disorganization and pulpal inflammation as compared to Biodentine. ConclusionTheraCal LC proves to be a promising future as a direct pulp capping agent.